A multi‐center international study of acupuncture for lateral elbow pain ‐ Results of a randomized controlled trial. (30th June 2020) - Gadau, Marcus; Zhang, Shi Ping; Wang, Fu Chun; Liguori, Stefano; Li, Wei Hong; Liu, Wei Hong; Bangrazi, Sergio; Berle, Christine; Razavy, Shohreh; Bian, Zhao Xiang; Filomena, Petti; Hao, Yang; et al.
Abstract: Background: Lateral elbow pain (LEP) due to tendinosis is one of the most common musculoskeletal pains of the upper limbs, yet there is no satisfactory treatment. This study was an international, prospective, multi‐centre, randomized, controlled, clinical trial to evaluate the efficacy of acupuncture compared to sham laser in the treatment of LEP. Methods: The study used a parallel and stratified design (1:1 allocation using a computer‐generated sequence) and was participant‐, outcome assessor‐ and statistician‐blinded. Subjects from 18 to 80 years with unilateral chronic LEP (minimum three months) were recruited at four centres in Australia, China, Hong Kong and Italy. The treatment group received manual acupuncture at acupoints LI 10 and LI 11 on the affected side whereas the control group received sham laser acupuncture at the same acupoints. The primary endpoint was disabilities of the arm, shoulder, and hand (DASH) questionnaire score at the three‐week post‐treatment follow‐up visit. Three VAS scales (pain at rest, pain on motion and pain during exertion) were secondary outcomes measures. Ninety‐six subjects were allocated to either the treatment group ( n  = 47) or control group ( n  = 49) and were all included in the analysis. Results: At the follow‐up visit, we found significant differences in DASH score between the two groups ( p  = .015). The median change to baseline for the treatment group was −11.7 (interval: −50.83 to 23.33), and for the control group −7.50 (interval: −36.67 to 29.10). The estimated effect size was 0.47, indicating a medium effect. Significant differences were also found for secondary outcome measures for VAS of pain. There were no severe adverse events. Our findings suggest that acupuncture has a moderate efficacy in the treatment of LEP. Conclusions: Acupuncture was shown to be efficacious in improving the function of the arm associated with lateral elbow tendinosis. Both the DASH score and the pain VAS on two occasions (at rest and during motion) showed a significant change over time indicating acupuncture as a potential treatment for LEP due to tendinosis.